Tiempo y eternidad en Tomás de Aquino. Reconstrucción y aproximación crítica. - Pulido Blanco, Jorge Enrique (Revista Estudios de Filosofía)
This article reconstructs Thomistic ontology centered on the actus essendi and asks whether Aquinas applied this approach in his philosophy of time. Our hypothesis is that, when he understands time from the perspective of eternity in the Summa Theologiae, he employs an ousiology of lesser explanatory capacity in relation to the existential ontology of De ente et essentia, thus leaving the most promising elements of his philosophy of time in a state of mere potentiality. Following with certain reservations Heidegger's critique of Aquinas's account of time, we seek to understand the reasons for this imbalance or disjunction between two such relevant themes. Finally, we propose three approaches by which it is possible to reconsider time from a Thomistic perspective more closely aligned with his existential ontology.